(untitled) - Lafore, Robert (Corte Madera, 1995)
Includes examples like: ELEV, VERYLONG, and PIPES; Covers the features of the C++ programming language including templates and exceptions; Fully compatible with Borland C++ 4.5 compilers
Keywords: Object-oriented programming (Computer science),C++ (Computer program language),Lập trình hướng đối tượng (Khoa học máy tính),C++ (Ngôn ngữ lập trình máy tính)